State Plan Proposals 1973-74 Government of West Bengal - Planning Commission (Planning Commission, 1972)
We would, like to invite the attention of the Planning Commission to certain special problems peculiar to West Bengal and summarised below;- The nigh rate of growth of population - 26.37 per cent in 10 years (I961-71) as against All-India average of 24.80 per has aggravated probe as. Population density now at 504 persons per (which is the second against Land) is against the All-India figure of 178 per Scheduled Castes and Scheduled Tribes constitute about 26 per cent West Bengal’s population.
Development and Planning Department
Government of West Bengal